Junctions of mass-deformed nonlinear sigma models on SO(2N)/U(N) and Sp(N)/U(N). Part II - Taegyu Kim; Sunyoung Shin (Journal of High Energy Physics, 2020)
Abstract We construct three-pronged junctions of mass-deformed nonlinear sigma models on SO(2N)/U(N) and Sp(N )/U(N ) for generic N. We study the nonlinear sigma models on the Grassmann manifold or on the complex projective space. We discuss the relation between the nonlinear sigma model constructed in the harmonic superspace for- malism and the nonlinear sigma model constructed in the projective superspace formalism by comparing each model with the N $$ \mathcal{N} $$ = 2 nonlinear sigma model constructed in the N $$ \mathcal{N} $$ = 1 superspace formalism.